The Effect of (CROSS FIT) Exercises on Fatigue Indicators and Rovey Among Young Basketball Players. - Abdel-Nabi Mohamed Hewitt, Mohamed (International Journal of Psychosocial Rehabilitation, 2020)
The introduction and the importance of the research lie in the use of (CROSS FIT) exercises and knowing the extent of their impact on the fatigue and Rovi indicators for young basketball players, and the study aimed to identify the extent of the impact of training using (CROSS FIT - traditional exercises) in the indicators of fatigue and Ruvi among young basketball players, and approach The researcher is the experimental research methodology on a sample of youth basketball players, and the number of the sample individuals reached (12) players, which were divided into two groups so that the first group is trained in (CROSS FIT) exercises and the second group uses the exercises prepared by the coach, for a period of 32 / 3/2019 until 5/30/2019, and after applying the tests under research and implementing the exercises prepared by the researcher and conducting the post-tests, their results were statistically processed using the Statistical Bag System for Social Sciences (SPSS) version (V24), then the researcher concluded that the exercises using (CROSS FIT) improved the fatigue and Rovi indications for young basketball players.